In situ Delivery of Thermosensitive Gel-Mediated 5-Fluorouracil Microemulsion for the Treatment of Colorectal Cancer [Corrigendum] - Wang L; Huang S; Guo H; Han Y; Zheng W; Jiang J (Dove Medical Press, 2020)
Wang L, Huang S, Guo H, Han Y, Zheng W, Jiang J. Drug Des Devel Ther. 2016;10:2855– 2867. The authors have advised there are errors in Figures 8 and 10 on pages 2864 and 2865, respectively. During image processing, an automated labelling step resulted in the insertion of incorrect images. As a result, in Figure 8, reporting the drug rectal retention time, an incorrect panel was used for inclusion in the TG-5FU-ME group. In Figure 10, reporting the morphology of rectal tissues after exposure to 5FU thermosensitive gel and TG-5FU-ME, incorrect panels were used for inclusion in the two testing groups. These errors do not affect the interpretation of data or the conclusion of the study. The authors apologize for these errors. Read the original article